Analysis of Organizational Cultural Profile Gaps Using a Cultural Intelligence Web-Based Tool - Alexandru CĂPĂŢÎNĂ; Rym BOUZAABIA (Revista de Management Comparat International)
The performances of the companies involved in the globalization process are conditioned by their managers’ abilities to understand the cultural differences of their stakeholders, to assess the cultural profiles of their business partners and to promote the cultural synergy. Our paper emphasizes the results of a survey that we undertook in the field of Cultural Intelligence (CQ), by analyzing two cultural profiles from a Romanian company and a Tunisian one, using a CQ web-based platform. The answers provided by a sample of employees of each company were processed by the means of the CQ platform facilities. The cultural profiles assessment reveals the cultural gaps between two companies involved in the same type of activities but belonging to different countries and implicitly cultures.